Fabrication And Physical Characterisation Of Zinc Oxide Thin Films - Lim , Yam Tee (2012)
Zinc oxide (ZnO) thin films were deposited on α-0001 sapphire substrates using direct current (d.c.) magnetron sputtering process and annealed at various temperatures in an inert atmosphere to investigate its effect on the ultraviolet (UV) emission, stress, lattice constants, crystallite size as well as the possibility of inducing nanostructure growth. Scanning electron microscope (SEM) and X-ray diffraction (XRD) found that ZnO thin films have a fairly uniform granular surface structure with a preferential c-axis growth direction.